The effect of stearic acid on surface properties of elastomeric compositions based on butadienestyrene rubber - O. A. Dulina; A. D. Abramova; D. V. Sitnikova; A. M. Bukanov (Тонкие химические технологии)
It has been shown that stearic acid has specific effect on the formation of surface properties of butadiene-styrene rubber produced by polymerization in solution, and of rubbers based on it. When stearic acid content is up to 1 wt. parts per 100 wt. parts of rubber, surface tension of samples is reduced, and at higher content the surface tension is increased. These features can be useful in predicting the technological behavior of rubber compositions during their processing.